2004
DOI: 10.1542/peds.2004-0525
|View full text |Cite|
|
Sign up to set email alerts
|

Brain-Type Natriuretic Peptide in the Diagnosis and Management of Persistent Pulmonary Hypertension of the Newborn

Abstract: Our findings indicate that BNP levels are elevated in infants with PPHN but not in infants with other forms of respiratory distress not associated with PPHN. Elevated BNP levels in term or near-term infants with respiratory distress should increase the suspicion of PPHN. Serial determination may also be helpful in monitoring the clinical course of such infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 13 publications
9
78
1
8
Order By: Relevance
“…BNP levels have also been used to identify PPHN; Reynolds et al showed that an initial BNP level of >159 pmol/l has a specificity of 90% and a sensitivity of 100% in predicting PPHN. They reported (as our group also did in its study) a strong relationship between BNP and echocardiographic signs of increased pulmonary vascular resistance (69,70). With BNP and NT-proBNP being suggested as screening biomarkers, it is important to realize that congenital heart defects can also present themselves with PPHN and elevated BNP levels (71).…”
Section: Patent Ductus Arteriosussupporting
confidence: 61%
“…BNP levels have also been used to identify PPHN; Reynolds et al showed that an initial BNP level of >159 pmol/l has a specificity of 90% and a sensitivity of 100% in predicting PPHN. They reported (as our group also did in its study) a strong relationship between BNP and echocardiographic signs of increased pulmonary vascular resistance (69,70). With BNP and NT-proBNP being suggested as screening biomarkers, it is important to realize that congenital heart defects can also present themselves with PPHN and elevated BNP levels (71).…”
Section: Patent Ductus Arteriosussupporting
confidence: 61%
“…4,5 BNP may also be used to distinguish neonates with persistent pulmonary hypertension from those with parenchymal lung disease. 6 NTpBNP is an inactive by-product of BNP, which is more stable, and has a longer half-life. Reference ranges for NTpBNP in term neonates have been published, and its potential role in PDA diagnosis was recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…20 There are reports about the capability of BNP to differentiate respiratory distress syndrome from PHT in NBIs; this means that BNP measurement may tell the difference between patients with a purely respiratory condition and those with hemodynamic or cardiac compromise. 28 A strong correlation has been observed, in NBIs with PHT, among BNP, clinical severity, 29,30 and treatment response. 31 Baptista et al 32 studied BNP levels in patients with congenital diaphragmatic hernia (CDH) and observed an association among BNP levels, the severity of PHT, and mortality in this population.…”
Section: Discussionmentioning
confidence: 94%